2016
DOI: 10.4088/jcp.15m10063
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Use in First-Episode Psychosis

Abstract: This study has confirmed that the prescribing of clozapine is low, delayed, and preceded by dosing of antipsychotic drugs above maximum limits. Identification of the factors found to be associated with clozapine use may encourage clinicians to consider clozapine sooner in relevant patients in hopes of achieving early symptomatic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…They found that the mean duration between their initial treatment to the commencement of clozapine was 3.2 years, with approximately three trials of different antipsychotics prior. Older age at diagnosis, previous suicide attempt and positive family history of schizophrenia were significant positive predictors to the initiation of clozapine.In 2016, Tang et al reported a retrospective study conducted between 2001 and 2012 to investigate clozapine prescribing pattern in Singapore (C Tang et al, 2016)…”
mentioning
confidence: 99%
“…They found that the mean duration between their initial treatment to the commencement of clozapine was 3.2 years, with approximately three trials of different antipsychotics prior. Older age at diagnosis, previous suicide attempt and positive family history of schizophrenia were significant positive predictors to the initiation of clozapine.In 2016, Tang et al reported a retrospective study conducted between 2001 and 2012 to investigate clozapine prescribing pattern in Singapore (C Tang et al, 2016)…”
mentioning
confidence: 99%
“…Such a finding may prompt psychiatrists to consider a trial of Clozapine, a second-generation antipsychotic which is associated with better outcomes, but is typically not used as a first-line agent due to the increased need for monitoring and higher risk of adverse effects. 95–97 In such cases, clinicians departing from the standard of care may be protected under what some refer to as the “reasonable innovation rule,” which allows clinicians in the U.S. some degree of flexibility when they depart from the standard of care to conduct clinical innovations even if these innovations caused harm to patients. 98–101 The purpose of this rule is to allow clinicians to innovate to address a patient’s unique needs but, among other things, clinicians need to have carefully considered alternatives, and any available literature or evidence to suggest the innovative intervention might work.…”
Section: Clinic-level Challengesmentioning
confidence: 99%
“…One study examined the use of clozapine in a cohort of consecutive FES patients with a 2-year follow-up. 18 Although patients who received clozapine had more positive and negative symptoms at baseline, they managed to reach rates of remission and recovery similar to those who had never received clozapine, indicating additional effects of clozapine for FES. Another study showed a robust response to clozapine for FES patients who had not responded well to initial trials of second-generation antipsychotic drugs.…”
mentioning
confidence: 93%